2014
DOI: 10.15282/ijame.9.2013.15.0137
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Modeling of Grinding of Ductile Cast Iron using Water Based SiO2 Nanocoolant

Abstract: This paper presents optimization of the grinding progress of ductile cast iron using water-based SiO 2 nanocoolant. Conventional and water-based nanocoolant grinding was performed using a precision surface grinding machine. The study is aimed to investigate the effect of table speed and depth of cut on the surface roughness and material removal rate (MRR). Mathematical modeling is developed using the response surface method. An artificial neural network model is developed for predicting the surface roughness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…As the correlation coefficient approaches 1, the accuracy of the prediction advances. Thus, the correlation coefficient range is very close to 1, which consequently indicates excellent agreement between the experimental and the ANN predicted results [13].…”
Section: Resultssupporting
confidence: 64%
“…As the correlation coefficient approaches 1, the accuracy of the prediction advances. Thus, the correlation coefficient range is very close to 1, which consequently indicates excellent agreement between the experimental and the ANN predicted results [13].…”
Section: Resultssupporting
confidence: 64%
“…Additionally, a study by Javadi et al [12] found that the types of nanoparticles used also contributed to the thermal conductivity enhancement whereby Al 2 O 3 and TiO 2 were found to have higher enhancement than SiO 2 . Also, thermal conductivity was affected by particle size and the stability of the nanofluid [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of nanofluids as coolants is mainly because of their enhanced thermal conductivity due to solid particles inclusions [43][44][45][46] and the convection heat transfer coefficient of the fluid can be greatly improved by nanoparticles suspensions [47][48][49][50][51]. Nanofluids can be conveyed to the cutting zone in a machining process through nozzles like flood cooling systems, but the higher manufacturing costs of nanofluids and large wastage during machining application [52][53][54][55] have prompted researchers to explore the greater potential of nanofluids incorporated with the principles of MQL. A lot of research on the application of nanocutting fluids has been reported in the literature about the use of nanoparticles as additives to traditional oil-based lubricants and the improved machining performance in terms of reduced wear and decreased friction.…”
Section: Introductionmentioning
confidence: 99%